1997
DOI: 10.1128/mcb.17.8.4363
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosomal Structures of c-myc Promoters with Transcriptionally Engaged RNA Polymerase II

Abstract: Organization of DNA into chromatin has been shown to contribute to a repressed state of gene transcription. Disruption of nucleosomal structure is observed in response to gene induction, suggesting a model in which RNA polymerase II (pol II) is recruited to the promoter upon reorganization of nucleosomes. Here we show that induction of c-myc transcription correlates with the disruption of two nucleosomes in the upstream promoter region. This nucleosomal disruption, however, is not necessary for the binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
3
14
1
Order By: Relevance
“…Interestingly, chromatin analyses of templates activated by TSA treatment also revealed only minor variations in chromatin structure. These findings are in agreement with other studies reporting little difference in the chromatin structure of nonexpressing, uninduced c-myc genes and that of highly expressing alleles, induced by sodium butyrate (1,42). In combination, our results implicate histone acetylation as a primary regulator of c-myc transcription in the Raji cell line.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, chromatin analyses of templates activated by TSA treatment also revealed only minor variations in chromatin structure. These findings are in agreement with other studies reporting little difference in the chromatin structure of nonexpressing, uninduced c-myc genes and that of highly expressing alleles, induced by sodium butyrate (1,42). In combination, our results implicate histone acetylation as a primary regulator of c-myc transcription in the Raji cell line.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, evidence supporting some form of elongational control in specific vertebrate genes has existed since the early 1980s, for example, greater nuclear run-on signals from 59 portions than 39 regions of chicken b-globin 32 . Similar data for mammalian c-Myc and c-Fos were augmented with in vitro studies that suggested initially a termination control further downstream, but more thorough characterizations in vivo showed these genes to have properties like those of Drosophila Hsp70 paused Pol II 33,34 .…”
Section: How General Is Paused Pol Ii?supporting
confidence: 56%
“…They found that they could drastically decrease both CTD phosphorylation and Pol II transcript accumulation in vivo using a highly specific inhibitor of P-TEFb, suggesting that P-TEFb is globally required for transcription. In vivo studies by Lis et al have demonstrated that P-TEFb is present at transcriptionally active loci in Drosophila (24), where it is located over the extent of the entire gene (2). This distribution contrasts with that reported for TFIIH, which, at least in vitro, is known to dissociate from the elongation complex soon after initiation (46).…”
contrasting
confidence: 44%
“…The guinea pig antiserum from the second or third bleed was used for immunoprecipitation and polytene immunofluorescence assays. Rabbit anti-heat shock factor (HSF) antibodies were produced as previously described (2). Rabbit anti-cyclin T antibodies were a gift from David Price.…”
Section: Fly Stocks Cdk7mentioning
confidence: 99%